Dating app use among rural men who have sex with men and its relationship to HIV prevention and risk behaviors: a mixed-methods analysis - Lauren Bineau; Danielle Lambert; Natalia Truszczynski; Nathan Hansen; Carolyn Lauckner (James Cook University, 2021)
Introduction: Men who have sex with men (MSM) in rural areas have limited access to HIV prevention and education resources. Given the growing usage of mobile dating apps among the wider MSM population, this research sought to explore their use among MSM in rural areas and their potential for delivering HIV prevention information. Methods: Participants were recruited from different areas of the rural Southern USA. This mixed-methods study consisted of an online survey (n=85) and follow-up qualitative phone interviews with 20 survey respondents. The survey assessed dating app use, sexual behaviors, and pre-exposure prophylaxis (PrEP) awareness, usage, and attitudes among MSM in the rural, Southern USA. Interviews explored perceptions of dating apps and their potential value as a source of health and HIV prevention information. Results: Among survey respondents, 74% had used a dating app, with Grindr being the most frequently used app. Of individuals who were in a relationship, 41% had met their current partner online. Using a dating app was associated with having a greater number of sexual partners. Three-quarters of participants had heard of PrEP, but only 7% had ever received a prescription for it and less than one-third reported that it would be easy to get PrEP if they wanted it. Dating app users were more likely than non-app users to have more positive attitudes toward taking PrEP and interest in taking PrEP. In qualitative interviews, respondents expressed support for integrating HIV prevention information into dating apps. Conclusion: Dating app usage is high among rural MSM. Individuals who use these apps have more sexual partners and also are more interested in PrEP for HIV prevention, suggesting that this is an ideal group to target for PrEP education and interventions. This could be especially beneficial for MSM in rural areas, as most have difficulty accessing PrEP and PrEP education.